Social media in human resources management - Bondarouk, Tanya, 1967-; Olivas-Lujan, Miguel R. (Emerald, 2013)
Social media have radically shifted the way people relate with each other and with organizations in technology-mediated ways; few areas are being impacted more strongly than Human Resources or Personnel Management. Attraction of candidates, internal communication with employees, communication with and among people; creation, design, testing and promotion of new services, new ways of organizing are appearing and changing the landscape at record speeds. This volume in the Advanced Series in Management utilizes empirical and theoretical approaches to shed light on this exciting set of emerging, stimulating new uses of technology that stretch creativity beyond conventional limits.
Keywords: Business & Economics -- Management.; Business & Economics -- Strategic Planning.; Business & management.; Business strategy.; Social media.; Personnel management.; elektronické knihy; electronic books